EFFECT OF FREQUENCY OF FEEDING HI-PRO-VITE 781N-1 ON THE GROWTH OF GOLDEN FISH (Cyprinus carpio) IN THE GOLDEN FISH BREEDING CENTER OF TOMONAMO IN LETEFOHO VILLAGE SUB DISTRICT SAME, MUNCIPLAITY OF MAUNUFAHI, TIMOR-LESTE - Salvador, Mateus; Belo, Cecilio Alves da Costa; Najamuddin, Najamuddin; Soares, Domingos; Magno, Marito (Ridwan Institute, 2024)
The purpose of this study was to determine the effect of the frequency of artificial feeding Hi-Pro-Vite 781N-1 on the effective growth of goldfish (Cyprinus carpio) in Timor Leste, Timor. The study used a complete randomized design (CRD) with 3 treatments and 3 replications, in which the conditions of the test unit are carried out according to randomization for all test units. The results of the research conducted for eight weeks (56 days) regarding the frequency for artificial feeding hi-pro-vite 780N-1 were: water temperature, water oxygen, sin water, and total dissolved solids (TDS) of 42.4 ppm, and the results of water quality measurements once a week in the morning (08.00 WIB), on average (20.00 htl) and in the afternoon (05.00) for 8 weeks (58 days). The results obtained during the research week (65 days) fresh at water temperature with a value of 20.2 oC with water oxygen 2.89 pmm, water content 8.3 pmm and TDS 42.4 pmm are indeed a good tolerance for the growth of carp fry (Cyprinus caprio). The behavioral impact of feeding frequency on carp growth and health is explored to refine feeding practices that promote well-being alongside growth. The findings could benefit feed manufacturers and aquaculture stakeholders by informing product development and feeding strategies tailored to maximize growth in carp, contributing to sustainable aquaculture practices. This study offers practical guidance for optimizing feeding practices to enhance growth efficiency, which is crucial for improving fish yield and farm productivity.